Protein Domain Annotation of Plasmodium spp. Circumsporozoite Protein (CSP) Using Hidden Markov Model-based Tools - Parikesit, Arli Aditya; Utomo, Didik Huswo; Karimah, Nihayatul (JURNAL BIOLOGI INDONESIA, 2018)
ABSTRACTPlasmodium sp. Circumsporozoite Protein (CSP) has a crucial role in sporozoite function and hepatocyte invasion. The basic understanding of this protein can reveal the mechanism of action. Protein domain annotation could determine the functional region of the specific protein. This study aimed is to identify the conserved and functional region of circumsporozoite protein using Hidden Markov Model approach. Three samples of CSP was retrieved from UniProt database; Circumsporozoite protein from Plasmodium vivax (P08677), Circumsporozoite protein from Plasmodium malariae (P13815), and Circumsporozoite protein from Plasmodium knowlesi (P02894). All sequenced was reviewed and could be used for further analysis. Multiple Sequences alignment (MSA) was used for analyzing the conserved region. CLUSTAL X software employed to run the MSA of circumsporozoite protein. Protein homology was clustered using MEGA 7.0, and domain annotation was done by the SUPERFAMILY hidden Markov models. The result showed that Circumsporozoite Protein has two specific conserved regions among species. This conserved region indicates the similar function and takes a vital role in their life cycle. Plasmodium  knowlesi and Plasmodium vivax had more similar sequence than Plasmodium malariae. The clustering result based on Circumsporozoite Protein indicates that Plasmodium malariae may have distinct infection mode to the host. The CSP was identified has one domain in C-terminus. Domain family of  CSP was TSP-1 type 1 repeat with high reliability. It can be concluded that conserved domain of Circumsporozoite Protein could reveal its critical role in Malaria Disease. To this end, CSP could be a potential candidate for vaccine development. Keywords: Circumsporozoite, conserved domain, Plasmodium spp, TSP-1 type 1 repeat.